Analisis Faktor Higiene dan Sanitasi terhadap Kontaminasi Bakteri Salmonella Sebagai Faktor Risiko Penyakit Diare pada Jajanan Pentol di Lingkungan Sekolah Dasar Wilayah Kecamatan Palang - Fidya Mukhofifin; H. Miftahul Munir (Jurnal Ilmu Kesehatan dan Gizi, 2026)
School snacks are one of the food sources commonly consumed by elementary school children; however, they are at risk of microbiological contamination if not properly managed. One of the pathogenic bacteria that can contaminate food is Salmonella, which can cause diarrheal disease. This study aimed to analyze hygiene and sanitation factors of food handlers on Salmonella bacterial contamination in pentol snacks at elementary schools in Palang District, Tuban Regency. This study used an observational analytic design with a cross-sectional approach. The sample consisted of 20 pentol vendors and 20 pentol snack samples. Data were collected through observation using a hygiene and sanitation checklist and laboratory examination to detect the presence of Salmonella bacteria. Data analysis was initially planned using the Chi-square test; however, due to homogeneous results, the analysis was conducted descriptively. The results showed that most vendors had good hygiene and sanitation (85%) and sufficient (15%). Laboratory examination results showed that all pentol snack samples (100%) were negative for Salmonella bacteria. In conclusion, pentol snacks at elementary schools in Palang District were microbiologically safe from Salmonella contamination.